Efikasi Herbisida Amonium Glufosinatt Gulma Umum Pada Perkebunan Karet yang Menghasilkan [Hevea Brasiliensis (Muell.) Arg] - Nurjannah Yuliana Hastuti; Dad Resiworo J. Sembodo; Rusdi Evizal (Politeknik Negeri Lampung., 2015)
This research was aimed to determine the efficacy of glufosinate ammonium on weed in rubber plants and to know it composition change. Research was conducted in the PTPN 7 UU Way Galih, Tanjung Bintang, and Weed Laboratory, Agricultural Faculty, University of Lampung, during June – August 2013. The Research using randomized complete block design with 6 treatments(t1= 225 g ha-1; t2= 300 g ha-1; t3= 375 g ha-1; t4= 450 g ha-1; t5= mechanical control; t6= control/ no treatment) and 4 replications. Data obtained were analyzed using analysis of variant. Homogenity using Bartlet Tast and aditifity using Tuckey Test. Differences in median tested using Least Significant Differenc (LSD) level 5%.Results: (1) all treatments of ammonium glufosinate (225 – 450 gha-1) significantly reduced weed total, broad leaves, and Selaginella wildenowii for 12 Weeks After Aplication (WAA). (2) Ottochloa nodosa and Grasses can be controlled only in higest dosage level of ammonium glufosinat (450 g ha-1) at 4 WAA. (3) Cyrtococcum acrescens can’t be controlled by treatments of ammonium glufosinate herbicide (225 – 450 g ha-1). Keywords : Ammonium glufosinate, weed, Hevea brasiliensis.